The Evaluation of 2013 Christian Religious Education Curriculum: Using the Stake Model Approach - Hendrik A.E Lao; Ezra Tari; Yohanes Baun; Hengki Wijaya (STAI Hubbulwathan Duri, 2022)
The author investigates the 2013 curriculum because student achievement is still very minimal. The purpose of this study was to analyze the initial context evaluation of the application of the 2013 Curriculum in Christian Religious Education, to analyze the evaluation of the application of the 2013 Curriculum in Christian Religious Education, to analyze the evaluation results of the 2013 Curriculum implementation of Christian Religious Education in SMA Negeri 6 Kupang, East Nusa Tenggara . The research method used in this research is the qualitative approach with the Countenece Evaluation Model evaluation model developed by Stake. The results of the research related to the implementation of the 2013 curriculum on Christian religious education subjects, it can be concluded that in the implementation of the 2013 curriculum teachers must have readiness in implementing learning in schools because in the 2013 curriculum students are required to be more active so that in preparing the material they must really master the material taught. Structured training on the 2013 curriculum has not been carried out to the fullest so teachers work in accordance with only the knowledge they have. While the KKM value in the eyes of the pursuit of Christian religious education that not all of them have achieved the predetermined KKM value.